The Goat-Gland Doctors of Rosalia - Jan Farrar (Symphony in the Flint Hills, 2014)
Many Kansans are familiar with the name John R. Brinkley, notorious doctor from Milford, known for his goat-gland transplant procedure in the early 1900s. However, few are aware that the smalltown of Rosalia has ties to his name and, more specifically, his chief surgeon, O. M. Owensby.
Keywords: goat; gland; operation; quack; transplant; testicles; impotence; male; Rosalia; Brinkley; hospital; Liggett Hotel; Owensby Sanitorium; malpractice; Great Depression; Smalltown; rural; business; Brinkley Hospital